Factors associated with clinical competency of nursing students - Yoeum, Bonsak; Koy, Virya; Sam, Rany (International Journal of Research in Medical Sciences, 2024)
A critical priority and challenge in nursing education today is caused by the variability of the healthcare environment. This systematic review reported findings on the independent variables that are associated with nursing students' clinical competency. A literature review search was conducted using Mendeley’s website in 2023 with using keywords such as nursing clinical competency and nursing student. The Mixed Methods Appraisal Tool (MMAT) was used to appraise and describe the methodological quality. A narrative report was given on the synthesis of the results. Based on the inclusion and exclusion criteria, 16 papers were retained out of 1162 identified research publications. Among 16 papers, the common predictive factors mentioned in the reviewed articles on the clinical competency of nursing students include clinical learning environment, self-efficacy, and self-awareness. Other factors such as clinical training program, type of learning-teaching, learning experiences, and socio-demographics were involved as the significant variables toward clinical competency. There are several other characteristics or predictors of clinical competency that require further investigation.